The Virtual World and Psychological Reality: Examining the Impact of Social Media on Gender and Psychological Well-being - Kinanti, Tira (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Social media has become an important part of daily life, especially for adolescents and young adults, encompassing communication, self-expression, and identity formation. Studies in Indonesia show that social media affects psychological well-being, particularly among women. This study aims to review the literature regarding the impact of social media on psychological well-being based on gender differences. This research uses a literature study method by searching for publications between 2020 and 2025. The results show that social media affects psychological well-being. Negative impacts are related to excessive use, social comparison, and the internalization of ideal standards, while factors such as self-compassion, emotion regulation, and social support act as protective factors. The findings also show gender-based differences, indicating that women are more often associated with body dissatisfaction and men with masculinity pressure. As an intervention, this study recommends a gender-sensitive multidisciplinary approach, including digital literacy and the practice of mindfulness and self-compassion to improve psychological resilience by promoting better self-awareness and self-acceptance. This approach is expected to serve as a preventive strategy in addressing gender-based social media challenges.